Training for 800m - Bennett, S.
Steady Training runs may be best done on rough uneven surfaces to encourage the use of a greater range of muscle fibres than the stimulus presented by a constant smooth surface like road or bike path. Certainly the African athletes train mostly on uneven surfaces. Athletes need endurance in a great range of muscles across the entire fibre spectrum. Avoid frequent doses of long contact time running eg Sand,Hills it may cause the athlete to change their motor pattern in such a way as too decrease stride frequency at all running speeds. The change in running biomechanics will happen over a long period of time and decrease efficiency. A focus on maximum strength in the legs while aiming to increase VO2max may inhibit the desired development due to conflicting training stimulus eg High Lactate in muscles effecting Aerobic enzymes. Improving strength in the upper body and trunk may be more acceptable and desirable. However recognize that each Kg may slow down an athletes. Race time over 5000m by about 3s per Kg. The muscle that is gained needs to be worthwhile. Training focus needs to be stimulating improvements in relaxed speed. Relaxation needs to be practised constantly. An athlete that can relax at 51.0 in a fast male 800m may have more useable speed than an athlete that is faster over 400m but is not relaxed at 51.0 speed. Efficiency is the name of the game. Athletes need to be able to change their style and change gears. This needs to be practised on a regular basis throughout the year.